Clinical and Financial Implications of Positive Margins After Nonmelanoma Skin Cancer Resection: A Longitudinal Evaluation. Issue 1 (July 2021) - Ranganath, Bharat; Teixeira, Robert M.; Patel, Tyag; Garza, Ramon; Murphy, Robert X.
Abstract : Background: Management of positive margins after nonmelanoma skin cancer (NMSC) excision is debated in the literature. The purpose of this study is to determine the rate of residual tumor in reexcised NMSC specimens after previous excision with positive margins, to determine the rate of recurrence in patients who had positive margins but did not undergo reexcision, and to define the financial burden of negative reexcisions. Methods: An Institutional Review Board-approved retrospective review was conducted on all patients with NMSC excision over a 15-year period. Patients who met inclusion criteria and underwent initial NMSC excision with negative frozen section margins, but had positive permanent section margins were divided into 2 groups: those who underwent reexcision for clearance of tumor (n = 161) or those who did not undergo further reexcision (n = 105). Variables collected include demographics, previous skin cancer, tumor location, cancer subtype, excision measurements, and time between first and second excisions. For those patients who did not undergo reexcision, charts were examined for recurrence. Results: Two hundred sixty-six patients met inclusion criteria with mean follow-up of 60 months. Eighty-three (52%) of 161 patients with positive margins on initial excision had no evidence of residual cancer upon reexcision. Residual tumor on permanent section was confirmed in 48% of patients. Patients with a previous history of basal cell carcinoma were more likely to have a true-positive margin after reexcision ( P = 0.02). Larger reexcisions were more likely to harbor residual cancer (5.9 cm 2, P = 0.04). Patients with positive margins that did not undergo reexcision, only 7 of 105 patients (6.6%) had recurrence. No mortalities were reported from NMSC recurrence. US $247, 672 was spent in reexcision for negative margins in 98 patients for an average cost of US $2984 per case. Conclusions: Forty-eight percent of NMSC patients with positive margins had residual tumor upon reexcision. There were 6.6% of the patients who did not undergo resection after positive margins developed recurrence of disease at 5 years. Patients requiring larger reexcisions or those with a prior history of BCC were more likely to have residual cancer upon reexcision. This study suggests that observation is an appropriate option of care for certain patients with residual NMSC on permanent pathology.